The Case of the Italian Mafia in the Types of State Terrorism - Perruca Albadalejo, Victoriano (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
In this job we are trying to Know what is the definition of governmental terrorism and his several kinds in order to making the Italian mafia up when it was trialed just in a context of international crime and according to general opinion some experts.